The archive of the Szwojnicki family in Borkłojnie - Mycio, Andrzej (Folia Toruniensia, 2017)
In 2004 the University Library in Torun received a small collection of archival materials including the private archive of the Szwojnicki family, who had owned the landed estate of Borkłojnie in Lithuania of Kaunas until WWII. The materials collected by the generations of the Szwojnicki family allow us to outline the history of the family. They were a family of landed officials. In the 19th century their estate of Borkłojnie was where Polish military units found shelter and food during the January Uprising. In 1897 Zygmunt Szwojnicki started to administer the estate, which he continued until the end of WWII. In the interwar period he was actively involved in the struggle for the maintenance of the Polish identity by Poles residing in the Republic of Lithuania. In 1946 he was resettled to Poland. The whole archive of the Szwojnicki family preserved in the University Library in Torun constitutes one of the minor archival collections of the library. It includes 12 inventory units. The oldest document in the collection comes from 1531, while the most recent one from 1946, which means the archival documents had been collected throughout almost 400 years. They record the history of the Szwojnicki family and their estate of Borkłojnie. The collection is a typical example of family files of the moderately well off Polish noblemen residing in Lithuania. The collection includes mainly documents confirming the family’s rights to bear the noble title and to own the landed estate, birth certificates, last wills, financial documents, biographic materials concerning the last owner of Borkłojnie – Zygmunt Szwojnicki.